2006
DOI: 10.1213/01.ane.0000184115.57837.30
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Bispectral Index Monitor for Measuring the Depth of Sedation in Children

Abstract: The Bispectral Index (BIS) is an empirically calibrated number derived from adult electroencephalograph data that correlates with the depth of sedation in adults. We tested the hypothesis that the BIS score is a valid measure of the depth of pediatric sedation in a study designed to avoid limitations of a previously published report. BIS values from 96 healthy ASA physical status I-II children aged 1-12 yr undergoing sedation were continually recorded and electronically transferred to a computer. Two independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 25 publications
2
65
0
4
Order By: Relevance
“…These results are consistent with previous studies that validated the BIS against UMSS in sedated children. 15,24 There has been only 1 other study utilizing the BIS for oral sedation of pediatric dental patients. Religa et al 28 found an association between BIS values and behavior during oral sedations, using the AAPD sedation guidelines, which are a scale based on behavioral responsiveness to stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies that validated the BIS against UMSS in sedated children. 15,24 There has been only 1 other study utilizing the BIS for oral sedation of pediatric dental patients. Religa et al 28 found an association between BIS values and behavior during oral sedations, using the AAPD sedation guidelines, which are a scale based on behavioral responsiveness to stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Patients received incremental doses of morphine 0.05 mg/kg at the end of surgery titrated to respiratory rate (RR) of 16-18/min after discontinuation of remifentanil infusion. Depth of anesthesia was monitored using Bispectral Index (BIS ® ) XP (Aspect Medical Systems, MA, USA) [18] or electroencephalography criteria by the intraoperative neuro monitoring team, a standard monitor for these surgeries. Post operatively, they received morphine through PCA.…”
Section: Perioperative Protocol and Clinical Outcomes Data Collectionmentioning
confidence: 99%
“…The COMFORT scale appears to be the most suitable for use in critically ill children [13,[16][17][18]23] and the University of Michigan scale for the evaluation of sedation during procedures [21].…”
Section: Clinical Scalesmentioning
confidence: 99%
“…Use of BIS during procedures that require sedation in children Several studies have demonstrated the utility of BIS to control the level of sedation when performing invasive procedures in children, finding a good correlation with clinical scales such as the sedation agitation scale, Ramsay Scale, and University of Michigan scale [10,21,36,37]. Values of BIS around 70 are considered appropriate [32].…”
Section: Bispectral Indexmentioning
confidence: 99%